Relatório de estágio curricular supervisionado em medicina veterinária – bovinocultura de corte - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This report aims to describe and discuss the activities developed or followed up during the Curricular Internship Supervised in Veterinary Medicine in the area of Beef Cattle, in the Genetic Agricultural Farm (GAP) located in the city of Jaciara, Mato Grosso, Brazil. The internship took place from January 15 to May 10, 2019, totaling a total workload of 632 hours, under the guidance of Prof. Dr. Tiago Gallina Corrêa and supervision by Veterinarian Jorge Luiz Oliveira Santana, Veterinarian responsible for the administration and management of the property. O internship included activities related to rural management, nutritional management, reproductive management, sanitary management and surgical techniques. It was also possible follow the general management routine of beef cattle on a cycle farm closed, which involve breeding, breeding and finishing, with a focus on the production of bulls and matrices of high genetic and racial value, adapted to different climates, for commercialization and expansion of breed breeding to other states.
Report of supervised internship in veterinary medicine - beef cattle
Keywords: Medicina veterinária; Bovinocultura; Bovinocultura de corte; Genética veterinária; Manejo de grandes animais; Clínica de grandes animais; Clínica médica veterinária; Clínica veterinária; Veterinary medicine; Cattle; Beef cattle; Veterinary genetics; Management of large animals; Large animal clinic; Veterinary medical clinic; Veterinary clinic; CNPQ::CIENCIAS AGRARIAS